2018
DOI: 10.1021/acs.inorgchem.8b01913
|View full text |Cite
|
Sign up to set email alerts
|

Chirality Induction in Crystalline Solids Containing Sandwich-type [Ln(α2-P2W17O61)2]17– Polyoxotungstates and Proline

Abstract: Chiral crystalline compounds of the series of [Ln­(α2-P2W17O61)2]17– polyanions embracing nearly all the lanthanide (Ln) ions were successfully isolated using Pro (proline) as a chiral director. In each compound, the polyanion and Pro were associated through a stereoselective interaction involving N­(H)···O hydrogen bonding. 31P NMR and circular dichroism studies revealed the induction of chirality by Pro in the racemic aqueous systems of the [Ln­(α2-P2W17O61)2]17– polyanions, i.e., the Pfeiffer effect. Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…[4] Since then, the field of Ln-POMs has expanded enormously, and they now can be classified into three main subclasses: (a) polyanions comprising a single Ln III center; (b) species incorporating several segregated Ln III ions and (c) polyanions integrating a polynuclear oxo/hydroxo cluster of lanthanide ions or both lanthanide and transition metal ions stabilized by lacunary POMs as auxiliary ligands. Representative examples include (a) [Yb III As 2 W 20 O 68 (H 2 O) 3 ] 7À , [5] [Ln III (H 2 O)P 5 W 30 O 110 ] 14À , [2,6] [Ln III (α 2 -P 2 W 17 O 61 ) 2 ] 17À ; [4,7] (b) [{(H 2 O) n Ln III (α 2 -P 2 W 17 O 61 )} 2 ] 7À , [8] (Ln = Tb, Eu), [9] [Ce III 16 As III 12 W 148 O 524 (H 2 O) 36 ] 76À , [10] [Ce III 20 Ge 10 W 100 O 376 (OH) 4 (H 2 O) 30 ] 56À ; [11] (c) [{Yb III 6 (μ 6 -O)(μ 3 -OH) 6 (H 2 O) 6 }(P 2 W 15 O 56 ) 2 ] 14À , [12] [Ce IV 7 Ce III 3 O 6 (OH) 6 (CO 3 )(H 2 O) 11 (P 2 W 16 O 59 ) 3 ] 19À , [13] [Ln III 27 Ge 10 W 106 O 406 (OH) 4 (H 2 O) 24 ] 59À (Ln=La, Ce) [14] and [{M II -(piperazine) 2 } 2 {Ln III 29 Ge 10 W 106 O 406 -(OH) 4 (H 2 O) 28 }] 49À (M=Cu, Co, Ni; Ln=La, Ce). [14] Due to the high magnetic moments combined with pronounced magnetic anisotropy of Ln III ions, caused by strong spin-orbit coupling, numerous Ln-POMs exhibit single-molecule magnet characteristics with high effective magnetization relaxation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Since then, the field of Ln-POMs has expanded enormously, and they now can be classified into three main subclasses: (a) polyanions comprising a single Ln III center; (b) species incorporating several segregated Ln III ions and (c) polyanions integrating a polynuclear oxo/hydroxo cluster of lanthanide ions or both lanthanide and transition metal ions stabilized by lacunary POMs as auxiliary ligands. Representative examples include (a) [Yb III As 2 W 20 O 68 (H 2 O) 3 ] 7À , [5] [Ln III (H 2 O)P 5 W 30 O 110 ] 14À , [2,6] [Ln III (α 2 -P 2 W 17 O 61 ) 2 ] 17À ; [4,7] (b) [{(H 2 O) n Ln III (α 2 -P 2 W 17 O 61 )} 2 ] 7À , [8] (Ln = Tb, Eu), [9] [Ce III 16 As III 12 W 148 O 524 (H 2 O) 36 ] 76À , [10] [Ce III 20 Ge 10 W 100 O 376 (OH) 4 (H 2 O) 30 ] 56À ; [11] (c) [{Yb III 6 (μ 6 -O)(μ 3 -OH) 6 (H 2 O) 6 }(P 2 W 15 O 56 ) 2 ] 14À , [12] [Ce IV 7 Ce III 3 O 6 (OH) 6 (CO 3 )(H 2 O) 11 (P 2 W 16 O 59 ) 3 ] 19À , [13] [Ln III 27 Ge 10 W 106 O 406 (OH) 4 (H 2 O) 24 ] 59À (Ln=La, Ce) [14] and [{M II -(piperazine) 2 } 2 {Ln III 29 Ge 10 W 106 O 406 -(OH) 4 (H 2 O) 28 }] 49À (M=Cu, Co, Ni; Ln=La, Ce). [14] Due to the high magnetic moments combined with pronounced magnetic anisotropy of Ln III ions, caused by strong spin-orbit coupling, numerous Ln-POMs exhibit single-molecule magnet characteristics with high effective magnetization relaxation barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Chirality is a common property of nature and refers to the phenomenon that the real substance cannot overlap with its mirror image. Such properties not only have important applications in pharmaceutical and biological science but also closely relate to spintronics, which is of great importance for quantum technology. Various drugs as well as many proteins and RNA are also chiral compounds, and thus, chirality plays an indispensable role in the fields of pharmacology, biology, and medicine . In particular, chiral materials exhibit an optical response to the circularly polarized light (CPL) described by circular dichroism (CD), which is defined as the differential absorption of left-handed and right-handed CPL. ,, Nevertheless, the variety of chiral inorganic matters that nature can provide to us is very limited.…”
mentioning
confidence: 99%
“…5−10 Various drugs as well as many proteins and RNA are also chiral compounds, and thus, chirality plays an indispensable role in the fields of pharmacology, biology, and medicine. 11 In particular, chiral materials exhibit an optical response to the circularly polarized light (CPL) described by circular dichroism (CD), which is defined as the differential absorption of left-handed and right-handed CPL. 9,12,13 Nevertheless, the variety of chiral inorganic matters that nature can provide to us is very limited.…”
mentioning
confidence: 99%
“…This material has a very open framework consisting of one unique cage [4 2 6 4 ] and two Reproduced with permission. [140] Copyright 2018, American Chemical Society. c) Combined polyhedral and ball-and-stick representation of noncovalently assembled chiral rod-like molecular triads of [Mo 6 O 18 NC(OCH 2 ) 3 MMo 6 O 18 (OCH 2 ) 3 CNMo 6 O 18 ] 7− , metals are Mn III (left) and Fe III (right).…”
Section: Zeolitesmentioning
confidence: 99%
“…[ 139 ] first found that the chiral lysine ligand could be coordinated to octamolybdate anions via carboxylate‐O atoms at the vacant sites. Iijima et al [ 140 ] obtained a chiral sandwich‐type [Ln(α 2 ‐P 2 W 17 O 61 ) 2 ] 17− (Ln = La, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Er, Tm, Yb, and Y) crystalline solid ( Figure a) assembled from polyoxotungstates and chiral Pro through electrostatic interaction and packing effects (Figure 10b). They found that the competitive enantiomeric interactions between the l ‐/ d ‐Pro and l ‐/ d ‐polyanions could regulate the racemization of POMs.…”
Section: Versatile Chemistry Of Chiral Ceramic Nanostructuresmentioning
confidence: 99%